Implementasi Karakter KedisiplinanSiswa Smk Negeri 2 Purwodadi - , Sutardjo, Prof.Dr. Sutama. M.Pd (2017)
ABSTRACT Sutardjo. Q. 100150066. Tittlele "Implementation of Dicipline Character for Students in SMK Negeri 2 Purwodadi". Tesis Pascasarjana Universitas Muhammadiyah Surakarta. 2017. The purpose of this study there are (1) describe the implementation of student discipline SMK Negeri 2 Purwodadi in learning. (2) describe the implementation of student discipline SMK Negeri 2 Purwodadi outside learning. Type this research qualitative research design and ethnography approach. Method of accumulation data with observation, interview, and documentation. Data analysis techniques with data accumulation, data reduction, data presentation, and conclusion. Test the validity of using triangulation. Research results there are (1) The implementation student of SMK Negeri 2 Purwodadi discipline character in learning activities with aspects: (a) The timely covering enter the classroom, learning activities, evaluation of learning, working and collecting of tasks end the teaching and learning activities. (b) Obedient the rules which include: participating in learning activities in an orderly manner, working orderly, learning activities according to schedule, the implementation of appropriate operational procedures of the school evaluation. (2) The implementation student of SMK Negeri 2 Purwodadi discipline character outside learning activities with aspects: (a) Time accuracy in outside learning include: following the ceremony and a morning assembly on time, sign and return to school on time, participate in sports, timely, following the timely extracurricular. (b) Obedient the rules following outside learning include: obedient the rules, no littering the trash, want to imitate the positive attitude of teachers, apply ethical manners well-dressed according to the rules, to be honest, no smoking, no drugs, and no fight. Keywords : discipline, character, implementation